Pulmonary Hypertension, Hypereosinophilia and Filariasis - Bambang Madiyono; Dede Kusmana; Otty W. Sonityo; O.J. Rachman (Paediatrica Indonesiana, 1978)
Reports have been made on three cases of pulmonary hypertension, hypereosinophilia with filariasis as the possible cause. Considering the Indonesian geographical location, it would be reasonable enough to perform further studies on hypereosinophilia cases. The possibity of filarial infestation is to be taken also into consideration. This condition should be treated as soon as possible to prevent or to slow down the consequences of continuing cardiovascular changes.